Cortico-limbic connectivity changes following fear extinction and relationships with trait anxiety - Belleau, Emily L (Soc Cogn Affect Neurosci, 2018)
Fear extinction is a powerful model of adaptive and anxiety-related maladaptive fear inhibition. This learning process is dependent upon plastic interactions between the amygdala, the anterior midcingulate cortex (aMCC), the hippocampus, and the ventromedial prefrontal cortex (vmPFC). With regard to the amygdala, the basolateral (BLA) and centromedial amygdala (CMA) serve unique roles in fear extinction. In a large sample (N = 91), the current study examined pre- to post-extinction changes in resting state functional connectivity (RSFC) of fear inhibition and expression pathways. We also examined how trait anxiety and extinction performance were associated with extinction-related changes within these neural pathways. We found stronger pre- to post-extinction RSFC in pathways known to play a role in the down-regulation of fear responses (BLA-hippocampus, aMCC-hippocampus, CMA-hippocampus, CMA-aMCC). We also found that trait anxiety was associated with strengthening of a BLA–aMCC circuit supporting fear expression following extinction learning. Furthermore, we found that physiological indices of poorer extinction learning were linked to weaker pre- to post-extinction RSFC of a BLA–hippocampus pathway important for fear extinction consolidation. Our results highlight the network changes that occur during extinction, the separable role of CMA and BLA-based circuitry and a key pathway linked to risk for anxiety pathology.